A Case Study of Kindergarten Teachers' Involvement in Three Years Old Children's Peer Conflicts - Batsaikhan, Javzandulam; Niannian, Nian (Southeast Asia Early Childhood Journal, 2025)
The objective of this study was to investigate how kindergarten teachers respond to peer conflicts among 3-year-olds, with the aim of identifying common patterns and distinguishing features in their interventions. The age of three is a unique transitional period when young children begin attending kindergarten as their first social setting. The study was conducted in Hangzhou in China, using a case study methodology and involved ten teachers from eight different kindergarten settings and 157 three-year old children in eight classes. The 120-observed record identified 214 peer conflicts, 54% of which were caused by object and space disputes; 18% by physical collisions; 16% by verbal disputes among young children; 12% by violations of disciplines and rules. Participating kindergarten teachers' approaches for resolving peer conflicts illustrated in the case study included (1) perfunctory response; (2) simple suppression; (3) authoritative determinations; (4) scientific guidance; and (5) objective factors influencing teachers' involvement (e.g., teacher children ratio; child characteristics; teacher child relationship; parent understanding and support; classroom management; inspection; co-teacher cooperation. Class size, curriculum, teacher-child connections, parental support, and teacher collaboration are some of the objective elements that affect kindergarten teacher participation, as are the professional attributes of teachers and their perspectives on education and children. Practical recommendations for kindergarten teachers' involvement in peer conflict among young children were given based on the research findings.